Landscapes and voices of the Great War
1 online resource (xxi, 496 pages)
Keywords: "This volume aims to provide a wider view of First World War experience through focusing on landscapes less commonly considered in historiography, and on voices that have remained on the margins of popular understanding of the war. The landscape of the Western Front was captured during the conflict in many different ways: in photographs, paintings and print. The most commonly replicated voicing of contemporary attitudes towards the war is that of initial enthusiasm giving way to disillusionment and a sense of overwhelming futility. Investigations of the many components of war experience drawn from social and cultural history have looked to landscapes and voices beyond the frontline as a means of foregrounding different perspectives on the war. Not all of the voices presented here opposed the war, and not all of the landscapes were comprised of trenches or flanked by barbed wire. Collectively, they combine to offer further fresh insights into the multiplicity of war experience, an alternate space to the familiar tropes of mud and mayhem"--Provided by publisher.